Legal Protection Gap for Persons with Disabilities in Indonesia: Literature Analysis of the Implementation of Law No. 8 of 2016 - Lianingsih, Nestia; Yuningsih, Siti Hadiaty (Communication in Research and Publications (CRP), 2025)
This study aims to analyze gaps in the implementation of Law Number 8 of 2016 concerning Persons with Disabilities in Indonesia. This law is an effort by the Indonesian government to provide more comprehensive legal protection for persons with disabilities, in line with the United Nations Convention on the Rights of Persons with Disabilities (UNCRPD). Using a literature analysis approach, this study identified five main gaps in the implementation of the law: limited physical and digital accessibility, lack of participation of persons with disabilities in the decision-making process, disparities in implementation at the regional level, unavailability of accurate data, and ongoing social stigma and discrimination. The research methodology is qualitative descriptive with secondary data sources in the form of literature, laws and regulations, government reports, journal articles, and other credible publications. The results of the study indicate that many public facilities are not yet fully disability-friendly, participation of persons with disabilities in policy forums is still minimal, there are gaps in implementation between regions, data on persons with disabilities has not been integrated, and negative stigma is still strong in society. Based on these findings, this study recommends strengthening accessibility regulation and monitoring, institutionalizing representation of persons with disabilities in policy-making, providing technical and budgetary assistance to reduce regional disparities, developing an integrated national database, and anti-stigma education campaigns. The implementation of these recommendations is expected to realize more effective legal protection and social inclusion for persons with disabilities in Indonesia.